Postsynthetic Metal and Ligand Exchange in MFU‐4l: A Screening Approach toward Functional Metal–Organic Frameworks Comprising Single‐Site Active Centers. Issue 22 (16th April 2015) - Denysenko, Dmytro; Jelic, Jelena; Reuter, Karsten; Volkmer, Dirk
Abstract The isomorphous partial substitution of Zn2+ ions in the secondary building unit (SBU) of MFU‐4l leads to frameworks with the general formula [MxZn(5–x)Cl4(BTDD)3], in which x≈2, M=MnII, FeII, CoII, NiII, or CuII, and BTDD=bis(1, 2, 3‐triazolato‐[4, 5‐b], [4′, 5′‐i])dibenzo‐[1, 4]‐dioxin. Subsequent exchange of chloride ligands by nitrite, nitrate, triflate, azide, isocyanate, formate, acetate, or fluoride leads to a variety of MFU‐4l derivatives, which have been characterized by using XRPD, EDX, IR, UV/Vis‐NIR, TGA, and gas sorption measurements. Several MFU‐4l derivatives show high catalytic activity in a liquid‐phase oxidation of ethylbenzene to acetophenone with air under mild conditions, among which Co‐ and Cu derivatives with chloride side‐ligands are the most active catalysts. Upon thermal treatment, several side‐ligands can be transformed selectively into reactive intermediates without destroying the framework. Thus, at 300 °C, CoII‐azide units in the SBU of Co‐MFU‐4l are converted into CoII‐isocyanate under continuous CO gas flow, involving the formation of a nitrene intermediate. The reaction of CuII‐fluoride units with H2 at 240 °C leads to CuI and proceeds through the heterolytic cleavage of the H2 molecule.